A 60 MeV proton beam-line dedicated to research and development programs. (June 2022) - Hofverberg, P.; Antunes, M.; Armando, C.; Bergerot, J.-M.; Bourrel, E.; Dicarlo, J.-F.; Donadey, G.; Dumas, S.; Fayaud, D.; Grini, J.-C.; Giusto, A.; Payan, Y.; et al.
Abstract: A new proton beam-line dedicated to R&D programs has been developed at Centre Antoine Lacassagne (CAL), in Nice (France), in collaboration with the Centre national d'études spatiales (CNES). This is the second beam-line of the MEDICYC 65 MeV cyclotron that is currently in operation, the first being the clinical 'eye-line' used for ocular proton therapy. The R&D beam-line is proposed with two configurations, the first producing a Gaussian narrow beam of a few mm width, the second a 100 mm diameter flat beam with a homogeneity better than ±3%. The energy range is (20 - ∼60) MeV, where the exact upper limit depends on the beam configuration being used. The energy spread of the non-degraded beam is (0.3 ± 0.1) MeV. A beam current between 10 pA and 10 μA can be produced with a stability better than 0.2% above 100 pA, and 2% below. The beam can be monitored online at a precision better than 5% in the flux range 1E5 (1E6) – 1E9 (1E10) p/cm 2 /s for a flat (Gaussian) configuration, although work is in progress to extend this range. Targeted applications for the R&D beam-line are instrumentation research, radiation tolerance tests of components and radiobiology. Highlights: A high-availability 60 MeV proton beam-line dedicated for R&D is operational. The beam-line can provide a 100 mm homogenous beam over a large flux interval. Alternatively, a Gaussian beam of a few mm standard deviation can be produced. The beam-line has been designed for radiation tolerance tests, instrumentation R&D and research in radiobiology.